Interactions between horse and rider that leads to a positive relationship - Skovgaard Licht Andersen, Simone (2015)
Horse riding is among the most dangerous sports, with more accidents happening than both football, motorcycle riding, rugby and skiing. The frequency of accidents increase with the frequency of being around horses (Equus ferus caballus), regardless of how experienced the rider is. This indicates that even professional riders are in the risk zone. The aim of this review is to clarify the factors affecting the interaction between horse and rider, and to investigate which training methods are most useful when training horses. This review concludes that the outcome of the interaction between horse and rider is affected by many factors, such as the riders seat and position, choice of training method, right equipment and knowledge of basic horse behavior. The interaction is also affected by the behaviour of the rider, which needs more research in future. This review also concludes that horses can be trained both by positive and negative reinforcement, but punishment should be avoided.